Recovery and purification of surfactin from fermentation broth by a two-step ultrafiltration process - Mohd Hafez Mohd Isa; Diego Esteban Coraglia; Richard A. Frazier; Paula Jauregi (Elsevier B.V., 2024)
Journal of Membrane Science 296 (2007) 51–57